2023
DOI: 10.1038/s41598-023-29605-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a reduced susceptibility to chlorfenapyr in the malaria vector Anopheles gambiae contrasts with full susceptibility in Anopheles funestus across Africa

Abstract: New insecticides have recently been produced to help control pyrethroid-resistant malaria vectors including the pyrrole, chlorfenapyr. Monitoring the susceptibility of mosquito populations against this new product and potential cross-resistance with current insecticides is vital for better resistance management. In this study, we assessed the resistance status of the major malaria vectors Anopheles gambiae and Anopheles funestus to chlorfenapyr across Africa and explored potential cross-resistance with known p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…L1014F-kdr mutation is negatively associated with resistance to IG2 whereas the L119F-GSTe2 mutation has no major impact In this study, a negative association was found between the kdrw mutation and mosquitoes' ability to survive exposure to the chlorfenapyr-based net IG2 (χ2 = 138; P < 0.0001) with RR mosquitoes most found in the dead. Such negative association noticed in this study could be attributed to the chlorfenapyr component in interceptor G2 as reported previously (44). This insecticide is considered as pro-insecticide that is activated by oxidase enzymes suggesting a potential for negative cross-resistance (45) as shown recently that mosquitoes bearing the 1014F-resistant allele were more vulnerable to chlorfenapyr (33) and clothianidin (46).…”
Section: Discussionsupporting
confidence: 85%
“…L1014F-kdr mutation is negatively associated with resistance to IG2 whereas the L119F-GSTe2 mutation has no major impact In this study, a negative association was found between the kdrw mutation and mosquitoes' ability to survive exposure to the chlorfenapyr-based net IG2 (χ2 = 138; P < 0.0001) with RR mosquitoes most found in the dead. Such negative association noticed in this study could be attributed to the chlorfenapyr component in interceptor G2 as reported previously (44). This insecticide is considered as pro-insecticide that is activated by oxidase enzymes suggesting a potential for negative cross-resistance (45) as shown recently that mosquitoes bearing the 1014F-resistant allele were more vulnerable to chlorfenapyr (33) and clothianidin (46).…”
Section: Discussionsupporting
confidence: 85%
“…While the P450s identi ed by our screening results may be considered to be activating markers of chlorfenapyr activity, reduced susceptibility in some pyrethroid resistant populations in DRC, Ghana and Cameroon has been reported 42 . The reasons for the reduced susceptibility are unclear, but given the multiplicity of P450's present in mosquito genomes (> 100), it is feasible that detoxi cation by other P450s may be a factor.…”
Section: Discussionmentioning
confidence: 77%
“…Since then, several studies have been conducted in sub‐Saharan Africa to distinguish An. funestus group species and assess their susceptibility to commonly used insecticides (Dia et al, 2013; Tchouakui et al, 2023). The resistance of An.…”
Section: Resultsmentioning
confidence: 99%
“…gambiae, An. funestus resistance to insecticides has been less extensively investigated, though there is now evidence of resistance to the multiple classes of insecticides (Coetzee & Koekemoer, 2013;Knox et al, 2014) with the exception of chlorfenapyr (Tchouakui et al, 2022(Tchouakui et al, , 2023 and the neonicotinoid clothianidin, which was recently prequalified by World Health Organisation (WHO) for IRS (Fouet et al, 2020). In West Africa, An.…”
Section: Introductionmentioning
confidence: 99%